EFEKTIVITAS EKSTRAK DAUN NIMBA (Azadirachta indica A. Juss) DALAM MENGATASI SERANGAN LIRIOMYZA SPP PADA TANAMAN BAWANG MERAH LEMBAH PALU - Arfan; Ratnawati; Hasmari Noer; Lisa Indriani; Asli; Juhana (Jurnal Agrotech, 2019)
The purposes of this research the examine the effectiveness various concentrations neem leaf ekstract on the intensity of attack Liriomyza spp on shallot Lembah Palu variety . Field research was carried out in Guntarano Village, Tanantovea Subdistrict, Donggala Regency, Central Sulawesi. This research conducted from February to April 2016 .The experiment was done using Randomized Complete Block Design with three replications, consists of six treatments, i.e. P0 : control (without aplication neem leaf ekstract); P1: neem leaf ekstract 10 gr /litre; P2 : neem leaf ekstract 20 gr / litre; P3 : neem leaf ekstract 30 gr / litre; P4 : neem leaf ekstract 40 gr / litre; P5 : neem leaf ekstract 50 gr / litre. To find out the effect of threatment, the analysis of variance, and the real influence is continued with the standard ά = 0.05 BNT test. The results showed that use of seed and leaf extracts of neem plant can control Liriomyza spp attack, only 3,04 percent of attack rate and shallot Lembah Palu variety productivity is 3,02/area.